Measuring competition using the Profit Elasticity: American Suger Industry, 1890 - 1914 - Jan Boone; Michiel van Leuvensteijn (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2010)
The Profit Elasticity (PE) is a new competition measure introduced in Boone (2008). So far, there was no direct proof that this measure can identify regimes of competition empirically. This paper focuses on this issue using data of Genesove and Mullin (1998) in which different regimes of competition are identified. We derive a version of PE suitable for this data set. This competition measure correctly classifies the monopoly / cartel regime as being less competitive than both the price was regime and break-up of cartel regime.
Keywords: 330; competition; measures of competition; price cost margin; profit elasticity